A New Leaf of GA 2311 - Patton, Andrew J. (Novum Testamentum, 2025)
This note presents a new leaf of GA 2311 containing the text of Luke 16:23–17:6. The leaf, held in the Royal Library of Belgium (KBR) and catalogued in a convolute of fragments as MS. II. 2404, 4, was previously known as GA 2599. Its provenance contributes additional information about the history of this Byzantine manuscript of the Gospels.